Self-swabbing in coronavirus pandemic- A game changer which can be introduced in field - Bhandary, Satheesh Kumar; Aroor, Rajeshwary; Bhat, Vadisha; V, Mark Jittu; P, Sreesan (Indian Journal of Community Health, 2020)
COVID-19, the disease caused by the novel coronavirus, SARS-CoV-2, is a highly contagious infection known to spread rapidly, leading to severe consequences and disasters. Health care workers are at higher risk of getting the infection, during the process of diagnosis and treatment of patients with the disease. Worldwide, a lot of health care workers have lost their lives because of COVID-19 infection. Managing the COVID- 19 caseload is a real challenge to the health care system. For the diagnosis of COVID-19, both nasopharyngeal and oropharyngeal swabs are obtained to detect viral RNA. (1). A nasopharyngeal swab is more sensitive due to higher viral load in nasal secretions than oral secretions, which is similar to that of Influenza (2). Taking nasopharyngeal swab is a real challenge to the health care workers and also is uncomfortable for the patient. It also exposes the health care workers to aerosols. Moreover, the scarcity of personal protective equipment (PPE) is a real burden to the health care system.